Lutte contre le changement climatique et maîtrise de la demande d’énergie : introduction au dossier thématique - Loïc Aubrée; Iratxe Calvo-Mendieta (Développement Durable et Territoires)
This paper is the introduction to the special section « Combating climate change and controlling energy demand ». In december 2015 and july 2016 the journal Développement Durable & Territoires published a special section addressing climate change adaptation issues. In this special section, we focus on climate change mitigation, dealing with politics, programs and instruments. The aim is to reduce greenhouse gases, through multi-level actions: reducing the use of fossil energy sources, developping renewable energies, efficiency and energy sobriety. The papers go beyond the technical dimension and address interelations between technical devices, socio-economic dynamics and actors’ practices. Energy provision issues allow us to tackle teritorial contexts in the North and in the South, to consider different geographic scales and to observe interactions between energy politics and urban and spatial planing.